Payments for environmental services in Costa Rica: conservation and production decisions within the San Juan - La Selva Biological Corridor - Morse, Wayde C. (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), Turrialba (Costa Rica) University of Idaho, Moscow, ID (EUA), 2014)
Tesis (Doctorado) -- CATIE. Escuela de Posgrado, Turrialba (Costa Rica), University of Idaho, 2014